The Biggest loser 30-day jump start : lose weight, get in shape, and start living the Biggest loser lifestyle today! - Forberg, Cheryl (Rodale ; Distributed to the trade by Macmillan, 2009)
The experts and cast from "The Biggest Loser" television show guide dieters through a daily integration of healthy nutrition, fitness, and lifestyle changes that are easy to follow and produce real results.